SOSIALISASI PENANGGULANGAN TINDAK PIDANA JUDI ONLINE DIKALANGAN MUDA-MUDI KARANG TARUNA DESA GONILAN KECAMATAN KARTASURA KABUPATEN SUKOHARJO MELALUI PENGAKTIFAN PROGRAM KERJA ORGANISASI KARANG TARUNA - Eko Ari Wibowo; Nendy Akbar Rozaq Rais; Siti Rokhmah; Tino Feri Efendi; Nafi’uddin Fauzi Mahfudh; Kartika Cahyaningtyas; Muh Isra Bil Ali (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2026)
Online gambling is a criminal act in Indonesia. Online gambling crimes can have a negative impact on society at large. The high number of criminal cases in Indonesia has given us an idea of ​​the importance of efforts to combat online gambling crimes. The crime of online gambling needs to be addressed because it has a negative impact on society. Thus, we are trying to carry out direct outreach in Karang Taruna Gonilan Village. The socialization was carried out with the aim of providing a general and specific overview of the impact of online gambling crimes. We hope that with this outreach, online gambling crimes can be minimized. Keywords; Crime, Online Gambling, Prevention, Karang Taruna.